Impact of inulin on viability and storage stability of probiotic Lactobacillus plantarum TISTR 2075 in fermented rice extract - Savedboworn, Wanticha; Niyomrat, Sureeporn; Naknovn, Janyawan; Phattayakorn, Kriangkrai (Agriculture and Natural Resources, 2017)
The influence was determined of various concentrations of inulin as a prebiotic on the growth of probiotic Lactobacillus plantarum TISTR 2075 fermented in Plai Ngahm Prachin Buri rice extract. The supplementation of 2% inulin provided the highest viable cell number of 8.90 log colony forming units/mL after fermentation at 37 oC for 24 h. The storage stability of the probiotic strain could be considered in terms of the specific rate of cell death (k value). The supplementation of 2% inulin exhibited the lowest k value of 2.48 x 10-2/d (30.16% survival) and 8.03 x 10-2/d (7.84% survival) after storage at 4 oC for 52 d and 30 oC for 31 d, respectively. The total reducing sugar and free amino nitrogen profiles of all treatments decreased over the storage period.